Highly Efficient Asymmetric Conjugate Additions of Aldehydes with Vinyl Sulfones Using a Sulfonamide Organocatalyst - Miura, Tsuyoshi; Yuasa, Hiroki; Murahashi, Miho; Ina, Mariko; Nakashima, Kosuke; Tada, Norihiro; Itoh, Akichika (Synlett, 2012)
A sulfonamide organocatalyst promotes the asymmetric conjugate addition of branched aldehydes to vinyl sulfones to afford the corresponding adducts with all-carbon quaternary stereocenters in excellent yields with up to 95% ee.
Keywords: organocatalyst; conjugate addition; sulfonamide; vinyl sulfone; quaternary stereocenter